Phase-tunable equiatomic and non-equiatomic Ti-Zr-Nb-Ta high-entropy alloys with ultrahigh strength for metallic biomaterials. (1st August 2022) - Xiang, Tao; Du, Peng; Cai, Zeyun; Li, Kun; Bao, Weizong; Yang, Xinxin; Xie, Guoqiang
Highlights: The equiatomic and non-equiatomic Ti-Zr-Nb-Ta high-entropy alloys are prepared by altering the atomic ratios of the different phases. The grain size of bulk Ti25 Zr25 Nb25 Ta25 alloys is smaller than Ti-Zr-Nb-Ta fabricated by vacuum arc melting. The yield strength of bulk Ti25 Zr25 Nb25 Ta25 alloys with plasticity of 8.7 ± 0.2% is two-fold than that of it fabricated by vacuum arc melting. Compared with CP-Ti, Ti25 Zr25 Nb25 Ta25 HEAs possesses analogous biocompatibility. Abstract: The contradiction between the strength and ductility of metallic materials is a major scientific problem that has been researched for a long time. Dual-phase equiatomic and non-equiatomic Ti-Zr-Nb-Ta high-entropy alloys (HEAs) with super-high strength and excellent ductility have been successfully developed via mechanical alloying (MA) combined with spark plasma sintering (SPS) technology. This is adjusted by altering the atomic ratios of the different phases. X-ray diffraction (XRD) and transmission electron microscopy (TEM) were performed to confirm the dual-phase microstructure. After the SPS process, the average grain size of the aforementioned equiatomic Ti25 Zr25 Nb25 Ta25 HEAs (134 ± 50 nm) evaluated by electron back-scattering diffraction (EBSD) is smaller than that of the Ti-Zr-Nb-Ta HEAs (150 µm), which were fabricated using arc melting. According to the Hall-Petch formula, the grain boundary strengthening contribution in the Ti-Zr-Nb-Ta system is 33-fold higher than those fabricated using the arc-melting process. When the alloy phase comprises the equivalent dual-phase, equiatomic Ti25 Zr25 Nb25 Ta25 HEAs have good comprehensive performance compared to non-equiatomic Ti-Zr-Nb-Ta HEAs prepared using the same process. The yield strength of equiatomic Ti25 Zr25 Nb25 Ta25 HEAs (2212 ± 38 MPa) is two-fold higher than that of Ti-Zr-Nb-Ta HEAs (1100 ± 90 MPa) fabricated via arc melting. This can be attributed to the ultra-fine grain size. Notably, the equiatomic Ti25 Zr25 Nb25 Ta25 HEAs possess approximately the same biocompatibility as commercial pure Ti (CP-Ti), indicating that the equiatomic Ti25 Zr25 Nb25 Ta25 HEAs are provided with a possibility as an advanced biomaterial for the applications of the medical field. Graphical abstract: Image, graphical abstract .